2010
DOI: 10.1002/prot.22692
|View full text |Cite
|
Sign up to set email alerts
|

Current status of membrane protein structure classification

Abstract: For over 2 decades, continuous efforts to organize the jungle of available protein structures have been underway. Although a number of discrepancies between different classification approaches for soluble proteins have been reported, the classification of membrane proteins has so far not been comparatively studied because of the limited amount of available structural data. Here, we present an analysis of alpha-helical membrane protein classification in the SCOP and CATH databases. In the current set of 63 alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…3). A bundle formed of 4 alpha-helices represents one of the widespread protein folds; this is one of few folds which are found both in water-soluble and in membrane proteins [93]. Binding of two hemes has been shown to stabilize the fold [94]; it has been shown that of the half of the de novo four-helical proteins from designed combinatorial libraries could bind the heme [95].…”
Section: Evolution Of the Cytochrome Bc Complexes: From Membrane-amentioning
confidence: 99%
“…3). A bundle formed of 4 alpha-helices represents one of the widespread protein folds; this is one of few folds which are found both in water-soluble and in membrane proteins [93]. Binding of two hemes has been shown to stabilize the fold [94]; it has been shown that of the half of the de novo four-helical proteins from designed combinatorial libraries could bind the heme [95].…”
Section: Evolution Of the Cytochrome Bc Complexes: From Membrane-amentioning
confidence: 99%
“…Unlike most globular proteins, most membrane protein structures can be classified, independent of evolutionary relationships, into two main groups, “all-alpha” and “all-beta”, based on structural characteristics alone [51], [52]. One dominant characteristic is the requirement for stability within the nonpolar interior of the membrane, and this is reflected in recurring patterns of defined length hydrophobic segments, imposed by the physical constraints of alpha-helical or beta-strand secondary structure elements.…”
Section: Resultsmentioning
confidence: 99%
“…SCOP [11] and/or CATH [12] annotations could be obtained for 54 chains although only 24 chains had a classification in both databases. In accordance with the current approach adopted both by SCOP and CATH for transmembrane proteins [13], all proteins were treated as single domain proteins.…”
Section: Methodsmentioning
confidence: 99%
“…However, our comparative analysis of the structural classification of α-helical membrane proteins in these databases has shown that the fold definition initially developed for globular proteins is applicable to membrane proteins only to a limited degree [13]. We therefore suggested revising the fold definition for membrane proteins by incorporating more fine-grained structural features such as helix-helix interactions.…”
Section: Introductionmentioning
confidence: 99%